The questions of the interaction of airport paving of ground base with few layers - Прусов, Д.Е. (Proceedings of National Aviation University (archive), 2009)
The methodology and numerical realization are proposed for of stress-strain state determination of aerodrome pavement construction concerning to interaction with inhomogeneous multi-layer soil semi-space with weak soil strata presence.